2021
DOI: 10.1021/acs.iecr.0c05484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO Slaking on Silica Removal during Warm Lime Softening of SAGD Produced Water

Abstract: MgO is added during warm lime softening (WLS) to remove silica from steam-assisted gravity drainage produced water. Although it is a general practice in the oil sand industry to avoid MgO slaking to ensure maximum silica removal, there has been no study on how slaking of MgO affects silica removal. This work aims to understand the effect of MgO slaking on silica removal and silica removal mechanism by MgO. Silica removal by slaked and nonslaked MgO was studied at different pH values (8.0–11.3) with different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Under high pH (9.5–10.5) and high temperature (80–90 °C) conditions, it is reported that silica mostly exists as dissolved silicate and is negatively charged in SAGD produced water. ,, As mentioned earlier, silica can deposit on the surface of equipment as solid fouling layers . It is well known that the silica fouling can be exacerbated via forming silicates with the presence of divalent and trivalent cations such as calcium, aluminum, iron, and magnesium .…”
Section: Silica and Organics In Sagd Produced Watermentioning
confidence: 95%
See 3 more Smart Citations
“…Under high pH (9.5–10.5) and high temperature (80–90 °C) conditions, it is reported that silica mostly exists as dissolved silicate and is negatively charged in SAGD produced water. ,, As mentioned earlier, silica can deposit on the surface of equipment as solid fouling layers . It is well known that the silica fouling can be exacerbated via forming silicates with the presence of divalent and trivalent cations such as calcium, aluminum, iron, and magnesium .…”
Section: Silica and Organics In Sagd Produced Watermentioning
confidence: 95%
“…However, the silica removal mechanism has not been fully established . For silica removal using magnesium compounds during softening in SAGD produced water, two possible competing mechanisms of silica removal were proposed: adsorption onto freshly precipitated Mg­(OH) 2 or precipitation by forming magnesium silicate precipitates. , Different reaction conditions may make one mechanism predominate over the other. As shown in Table , pH, the type of magnesium compounds, and initial molar ratio of Mg:Si were the most significant factors affecting the silica removal mechanism by magnesium compounds compared to other parameters such as contact time, temperature, and initial silica concentration.…”
Section: Silica and Organics In Sagd Produced Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Silica and hardness removal are essential for the pretreatment of water prior to reverse osmosis (RO) desalination, as membrane scaling often limits the degree of water recovery under high pressure. , This need is accentuated with the push toward minimum and zero liquid discharge plants, where staged RO modules operate at higher recoveries. The most common methods for removing silica is through lime softening (Ca­(OH) 2 ), warm/hot softening, , and ion exchange membrane. Alum or ferric chloride can also be used for removing silica from water, and the typical percentage removal is 50–70%. The optimal dosage of chemicals depends on the silica concentration in water along with the presence of other chemicals (alum, lime) . Sodium aluminate is one of the most effective chemicals for silica removal and can remove 94.3% of silica when the aluminum loading is at 70 mg/L. , This is equivalent to a removal capacity of 0.21 mg of Si per mg of Al.…”
Section: Introductionmentioning
confidence: 99%